Predictors and outcomes of low birth weight in Lusaka, Zambia - Chibwesha, Carla J. (Int J Gynaecol Obstet, 2016)
OBJECTIVE: To determine factors associated with low birth weight (LBW) in an urban Zambian cohort and investigate risk of adverse outcomes for LBW neonates. METHODS: The present retrospective cohort analysis used data recorded between February 2006 and December 2012 for singletons and first-born twins delivered in the public health system of Lusaka, Zambia. Routine clinical data and generalized estimating equations were used to examine covariates associated with LBW (<2500 g) and describe outcomes of LBW. RESULTS: In total, 200 557 neonates were included, 21 125 (10.5%) of whom had LBW. Placental abruption, delivery before 37 weeks, and twin pregnancy were associated with LBW in multivariable analysis (P<0.01 for all). Compared with neonates weighing more than 2500 g, those with LBW were at higher risk of stillbirth (adjusted odds ratio [AOR] 8.6, 95% confidence interval [CI] 6.5–11.5), low Apgar score (AOR 5.7, 95% CI 4.6–7.2), admission to the neonatal intensive care unit (AOR 5.4, 95% CI 3.5–8.3), and very early neonatal death (AOR 6.2, 95% CI 3.7–10.3). CONCLUSION: LBW neonates are at increased risk of adverse outcomes, including stillbirth and neonatal death, independent of pregnancy duration at delivery and multiple pregnancy. These findings underscore the need for early, comprehensive, and high-quality prenatal care.